Effect of n- and p-doping on vacancy formation in cationic and anionic sublattices of (In,Al)As/AlAs and Al(Sb,As)/AlAs heterostructures - Shamirzaev, Timur S. (Nanomaterials)
The vacancy generation dynamics in doped semiconductor heterostructures with quantum dots (QD) formed in the cationic and anionic sublattices of AlAs is studied. We demonstrate experimentally that the vacancy-mediated high temperature diffusion is enhanced (suppressed) in n- and p-doped heterostructures with QDs formed in the cationic sublattice, while the opposite behavior occurs in the heterostructures with QDs formed in the anionic sublattice. A model describing the doping effect on the vacancy generation dynamics is developed. The effect of nonuniform charge carrier spatial distribution arisen in heterostructures at high temperatures on the vacancy generation and diffusion is revealed.